Learning Chinese? The changing investment behavior of foreign institutions in the Chinese stock market - Timo Korkeamäki; Nader Virk; Haizhi Wang; Peng Wang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
We analyze preferences of foreign institutional investors in the Chinese stock market in a sample that covers 2003 to 2014. We find foreign investors changed their investment behavior during the sample period from generic patterns found in much of the world to China-specific patterns. The results suggest that foreign institutions learned to adjust their investment behavior to account for unique features of the Chinese market.
URN:NBN:fi:bof-201811202134
Keywords: G11; G15; 330